Walkability Indicators in the Aftermath of the COVID-19 Pandemic - Jardim, Bruno (2022)
Jardim, B., & De Castro Neto, M. (2022). Walkability Indicators in the Aftermath of the COVID-19 Pandemic: A Systematic Review. Sustainability, 14(17), 1-24. [10933]. https://doi.org/10.3390/su141710933 - -----Funding: This research was funded by the Project C-TECH—Climate Driven Technologies for Low Carbon Cities, grant number POCI-01-0247-FEDER-045919 | LISBOA-01-0247-FEDER-045919, co-financed by the ERDF—European Regional Development Fund through the Operational Program for Competitiveness and Internationalization—COMPETE 2020, the Lisbon Portugal Regional Operational Program—LISBOA 2020 and by the Portuguese Foundation for Science and Technology—FCT under MIT Portugal Program. This work was also supported by Portuguese national funds through the Portuguese Foundation for Science and Technology—FCT under research grant FCT UIDB/04152/2020–Centro de Investigação em Gestão de Informação (MagIC).